Granulomatosis with Polyangiitis (Wegener's Granulomatosis) Accompanied by Dysuria. (13th March 2016) - Takeuchi, Hisashi; Kuroda, Isao; Takizawa, Issei; Aoyagi, Teiichiro; Tachibana, Masaaki
Abstract : A 65-year-old male visited us with complaints of retarded urination, dysuria, gross hematuria, and fever. Urinalysis showed pyuria. Prostatic tumor with lung metastasis was suspected from computed tomography and magnetic resonance imaging. Transurethral prostatic biopsy and bronchoscopic biopsy only revealed fibrinoid necrosis and inflammatory infiltration. Right lateral maxillary sinusitis was also found by MRI. ANCA testing was positive with specificity for anti-PR3 (PR3-ANCA). On the basis of these results, Granulomatosis with polyangiitis (GPA) was diagnosed. GPA involving the prostate gland is unusual, and only a few cases have previously been reported.